1997
DOI: 10.1111/j.1365-2044.1997.250-az0384.x
|View full text |Cite
|
Sign up to set email alerts
|

Convection warmers — not just hot air

Abstract: SummaryWe sought to determine whether the forced air convection warmers (nine Bair Huggers, Augustine Medical, and one Warm Touch, Mallinkrodt Medical) used in our operating theatres could be a source of microbial pathogens. Agar plates were placed directly in the air stream of the warmers. Four of these grew potentially pathogenic organisms. When the warmers were set to blow through perforated blankets, no growth occurred. Three of the warmers were swabbed and sites of colonisation were found in their hoses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 4 publications
0
41
1
3
Order By: Relevance
“…However, the correct use of microbial filters and the recommended perforated blankets has been shown to prevent their transmission [77]. Moreover, analysis of theatre air samples in positive pressure theatres has shown a significant decrease in bacterial counts when forced-air warming was used correctly [80].…”
Section: Forced-air Warming Device Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the correct use of microbial filters and the recommended perforated blankets has been shown to prevent their transmission [77]. Moreover, analysis of theatre air samples in positive pressure theatres has shown a significant decrease in bacterial counts when forced-air warming was used correctly [80].…”
Section: Forced-air Warming Device Safetymentioning
confidence: 99%
“…Evidence suggests that forced-air warmers may also harbour microbial pathogens that have the potential to be emitted into the operating theatre environment via the air warmer hose [77][78][79]. However, the correct use of microbial filters and the recommended perforated blankets has been shown to prevent their transmission [77].…”
Section: Forced-air Warming Device Safetymentioning
confidence: 99%
“…Unlike forced-air warming, there is no consumable associated with use of the heating pad, so the latter is cheaper in long-term use. For forced-air warming, the hose, the warming units and even the brand new commercial blankets have been shown to be potential sources of nosocomial infection [3][4][5]. The heating pad warming system, which comprises a control unit, an electric cable and a heating pad, has no hidden space for bacterial colonisation and is theoretically easier to clean.…”
mentioning
confidence: 99%
“…Further concerns exist about bacterial contamination of the forced-air system [110] . A possible transfer of microbial pathogens with the airstream into the surgical field has been described [2] ; however, several studies have challenged the clinical relevance of these findings and found no difference in bacterial dispersion with or without forced-air warming [5,46,120] .…”
Section: Forced-air Warmingmentioning
confidence: 99%